2017
DOI: 10.1186/s12887-017-0874-0
|View full text |Cite
|
Sign up to set email alerts
|

Stool frequency recording in severe acute malnutrition (‘StoolSAM’); an agreement study comparing maternal recall versus direct observation using diapers

Abstract: BackgroundApproximately 50% of the deaths of children under the age of 5 can be attributed to undernutrition, which also encompasses severe acute malnutrition (SAM). Diarrhoea is strongly associated with these deaths and is commonly diagnosed solely based on stool frequency and consistency obtained through maternal recall. This trial aims to determine whether this approach is equivalent to a ‘directly observed method’ in which a health care worker directly observed stool frequency using diapers in hospitalised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Although there is some subjectivity in determining a child’s medical condition that is “improving,” we chose stabilization as a main outcome rather than episodes of diarrhea because 1) it is the purpose of F75; 2) once a child switches to F100 or RUTFs, earlier transition could conceivably result in an increase in diarrhea unrelated to mF75 or F75; 3) diarrhea is very difficult to quantify objectively since maternal recall is not accurate in identifying episodes or severity [25]; 4) diapers may not distinguish every stool episode, and their weight is affected by urine; and 5) refeeding syndrome may be critical to early outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Although there is some subjectivity in determining a child’s medical condition that is “improving,” we chose stabilization as a main outcome rather than episodes of diarrhea because 1) it is the purpose of F75; 2) once a child switches to F100 or RUTFs, earlier transition could conceivably result in an increase in diarrhea unrelated to mF75 or F75; 3) diarrhea is very difficult to quantify objectively since maternal recall is not accurate in identifying episodes or severity [25]; 4) diapers may not distinguish every stool episode, and their weight is affected by urine; and 5) refeeding syndrome may be critical to early outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…The study was unable to ascertain the impact of perception bias and if participants truly understand what de nes a case of diarrhoea. For example, in a previous study, Voskuijl and colleagues (2017) found that parents of infants with severe acute malnutrition in a Malawian hospital were only able to identify 75% of loose or watery stools as such (loose or watery stools being identi ed by observation by a health care provider) [17].…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…2) The study was unable to ascertain the impact of perception bias and if participants truly understand what defines a case of diarrhoea. For example, in a previous study, Voskuijl and colleagues (2017) found that parents of infants with severe acute malnutrition in a Malawian hospital were only able to identify 75% of loose or watery stools as such (loose or watery stools being identified by observation by a health care provider) [16].…”
Section: Strengths and Weaknessesmentioning
confidence: 99%